Gluten-Free Diet Does Not Appear to Induce Endoscopic Remission of Eosinophilic Esophagitis in Children with Coexistent Celiac Disease - Joseph R Abraham; Rabin Persad; Justine M Turner; Hien Q Huynh (Canadian Journal of Gastroenterology)
BACKGROUND: Celiac disease and eosinophilic esophagitis are usually considered to be separate gastrointestinal diseases; however, it appears that they may coexist more often than would be expected. It is unknown whether eosinophilic esophagitis in patients with celiac disease responds to a gluten-free diet.